Responsibility, Taint, and Ethical Distance in Business Ethics - Mellema, G. (Journal of business ethics, 2003)
Much light can be shed on events which characterize or underlie scandals at firms such as Enron, Arthur Andersen, Worldcom, ImClone, and Tyco by appealing to the notion of ethical distance. Various inquiries have highlighted the difficulties in finding or identifying particular individuals to blame for particular events, and in the context of situations as complex as these it can sometimes be helpful to investigate the comparative ethical distance of various participants in these events. In this essay I offer a characterization of ethical distance in terms of moral responsibility, and in doing so I describe and illustrate the rough inverse correlation between moral distance and degrees of moral responsibility. I urge that the concept of ethical distance is capable of shedding light upon situations in which several people are involved in bringing about a state of affairs. I then argue that moral responsibility cannot do justice to all situations involving ethical distance. When the distance between a person and a state of affairs grows sufficiently large, a different type of treatment is called for, and I introduce the notion of moral taint to describe the moral status of agents in these situations.